Multi-omics analysis of canine aging markers and evaluation of stem cell intervention - Balun Li; Yanheng Ding; Miao Han; Zengyu Zhang; Zixi Ling; Wenlong Zhu; Xianjun Zhao; Yihua Zhang; Changrong Lv; Na Li; Mingzhi Liao; Jinlian Hua (Communications Biology)
Abstract Dogs serve as ideal research subjects for aging studies. In this study, 9 aging-related cell populations are identified through single-cell RNA sequencing of dogs of different ages. Additionally, 9 CD8+ T cell senescence-specific markers conserved across species are identified. Furthermore, multi-omics technology is employed to characterize 17 transcriptional and protein markers, along with 5 metabolic markers, associated with stem cell aging. Penitrem A and UDP-N-acetylglucosamine are further validated as two consistent metabolic markers of both individual and cellular senescence. A customized metabolic assessment system and blood-based assessment framework specifically for aging dogs are developed. Notably, it is demonstrated that mesenchymal stem cells, particularly those overexpressing NMNAT1, can delay or reverse aging in dogs. This study sheds light on the mysteries of aging from multiple perspectives and provides a broad target for future research efforts aimed at uncovering the complexity of this fundamental biological process.